Sustainable Entrepreneurship In MSMEs: A Systematic Literature Review On The Convergence Of Innovation, Digitalization, Competence, And Culture (2021-2024) - Esti Nurwulan; Titisari Ambarwati; Sudarmiatin; Trisetia Wijijayanti (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Sustainable Entrepreneurship (SE) integrates economic, social, and environmental objectives to meet the challenges of sustainable development while maintaining competitiveness. Micro, Small, and medium enterprises (MSMEs) play an important role in this transition, but face various obstacles such as limited resources, institutional constraints, and cultural rigidity. This study presents a Systematic literature Review (SLR) of cutting-edge research published between 2021 and 2024 and focuses on the determinants and mechanisms of sustainable entrepreneurship in MSMEs. Following the PRISMA 2020 framework, seven empirical and conceptual studies from Europe, Asia and Africa were analyzed. The synthesis shows the four main pillars that make up SE, namely entrepreneurial competence, innovation, digitization, as well as the cultural or institutional context. The results show that innovation and digitalization act as mediators that strengthen the relationship between entrepreneurial competence and sustainability performance. Cultural norms and government policies play contextual roles that can support or hinder their implementation. This study proposes an integrative framework that aligns entrepreneurial competencies, innovation, digital transformation, and policy support as strategic drivers for the sustainability of MSMEs. Theoretical, managerial, and policy implications are discussed, as well as recommendations for further research direction are given.